Compare the Effectiveness of Prostaglandin E2 Vaginal Gel Versus Vaginal Tablets for the Induction of Labour at Term (Medical Forum Monthly, 2024)
Objective: To compare the effectiveness of prostaglandin E2 vaginal gel versus vaginal tablets for the induction of labour at term.Study Design: Retrospective comparative studyPlace and Duration of Study: This study was conducted in Gynaecology and obstetric unit B, Lady Reading Hospital Peshawar, from 1st January 2013 till 31st December 2014.Materials and Methods: Study population was women with singleton, term pregnancy with cephalic presentation undergoing induction of labour after 37 weeks of gestation. Prostaglandin E2 (PGE2) vaginal tablets (3 mg) or vaginal (2 mg) was administered at 6-hourly intervals, two doses administered. Main outcome measured was rate of failed induction of labour, besides failed induction in primigravida and multigravida and mode of delivery was also observed in both groups. Descriptive statistics was used to analyze the data and the results are expressed in the form of frequency and percentages.Results: The number of patients induced with PGE2 tablet (3mg) were 39.74 % (n=503) while 60.20 (n=761) were induced with PGE2 gel (2mg). It was observed that failed induction was more in patients induced with PGE2 tablets 14.11 %( n=71) as compared to PGE2 gel 8.67% (n= 66). Sub analysis showed failed induction was more in primigravida as compared to multigravid women. Spontaneous vaginal birth was found to be the most common mode of delivery 75.31 %( n=952)Conclusion: Prostaglandin E2 vaginal gel is superior to vaginal tablets for the induction of labour.